Investigating bitumen's direct interaction with Tetradecane as potential phase change material for low temperature applications. Issue 8 (16th November 2020) - Kakar, Muhammad Rafiq; Refaa, Zakariaa; Bueno, Moises; Worlitschek, Jörg; Stamatiou, Anastasia; Partl, Manfred N.
Abstract : Temperature is significantly influencing the behaviour of asphalt road surfaces. In case of cooling, asphalt pavements become stiffer eventually reaching a brittle state at which thermal cracking may occur. Phase change materials (PCM) respond to the environmental changes by actively altering their own properties by absorbing, storing, or releasing heat without changing their own temperature. Nevertheless, the application of phase change materials in thermoplastic materials, such as asphalt, has drawn attention only recently. The current study aims with an innovative approach for buffering and controlling extreme low temperatures in asphalt road surfaces by incorporating PCM as an additive for storing heat energy in a latent form. However, the results showed that the addition of Tetradecane as raw PCM material into the bitumen 10/20, 70/100 and 160/220 drastically increased penetration and decreased the conventional characteristics such as softening temperature as well as the complex modulus. The results of this study reveal that the direct interaction of Tetradecane with bitumen significantly affects the rheological properties of bitumen without storing heat energy in a latent form. Therefore, the choice of a suitable PCM and its incorporation in bitumen (e.g. microencapsulation, shape stabilisation) and possible leakage of protected PCM due to breakage of shell is very important in the context of bitumen modification.